APLIKASI KASIR BERBASIS WEB TERINTEGRASI DENGAN LAPORAN PENJUALAN MENGGUNAKAN ALGORITMA FLUXSORT (STUDI KASUS: TOKO JOEL, KELURAHAN PUNGGOLAKA, KOTA KENDARI) - Laode Ikhwanul Uzlah; Statiswaty Statiswaty; Jumadil Nangi (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
Manual transaction recording in a business triggers calculation errors, difficulties in data retrieval, and delays in reporting. This study aims to develop a web-based cashier application by implementing the Fluxsort algorithm as a data sorting method at the application layer. The system is built using Python/Flask and an SQLite database, and operates offline on a local network. The Fluxsort algorithm is integrated to sort the product list in the Cashier module and sales aggregation reports in the Admin module. This approach effectively avoids repeated query latency on the database server and handles multi-table aggregation values. Functional testing results achieved a 100% success rate across 11 test scenarios. Performance testing proved that the Fluxsort algorithm is capable of completing the sorting of 1,000 random data entries in 16.508 milliseconds. Black Box Testing validated 20 interface scenarios with 100% valid results. User Acceptance Testing (UAT) involving 5 respondents yielded a feasibility index of 91% (Very Good). Therefore, this system is rated Very Feasible and reliable as a digitalization solution for MSME operational needs.